2022
DOI: 10.3390/polym14194216
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-vinylpyrrolidone)–Laponite XLG Nanocomposite Hydrogels: Characterization, Properties and Comparison with Divinyl Monomer-Crosslinked Hydrogels

Abstract: The present work investigates, for the first time, the synthesis and properties of some nanocomposite (NC) hydrogels obtained by the aqueous solution free radical polymerization of N-vinylpyrrolidone (NVP) in the presence of Laponite XLG (XLG) as a crosslinker, in comparison with the corresponding hydrogels prepared by using two conventional crosslinking divinyl monomers: N,N’-methylenebisacrylamide (MBA) and tri(ethylene glycol) divinyl ether (DVE). The structure and properties of the hydrogels were studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The images show a core‐shell structure consisting of LAM surrounded by copolymer compatible with MNP (core)‐polymer (shell) morphology 38,44 . This indicates that polymerization takes place from the outside of the monomer droplets to the inside 40,45–47 . From the contrast between the core and shell parts of LAM, the lighter parts indicate cross‐linked polymers and the darker parts indicate LAM nanoparticles 1,48 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The images show a core‐shell structure consisting of LAM surrounded by copolymer compatible with MNP (core)‐polymer (shell) morphology 38,44 . This indicates that polymerization takes place from the outside of the monomer droplets to the inside 40,45–47 . From the contrast between the core and shell parts of LAM, the lighter parts indicate cross‐linked polymers and the darker parts indicate LAM nanoparticles 1,48 .…”
Section: Resultsmentioning
confidence: 97%
“…38,44 This indicates that polymerization takes place from the outside of the monomer droplets to the inside. 40,[45][46][47] From the contrast between the core and shell parts of LAM, the lighter parts indicate cross-linked polymers and the darker parts indicate LAM nanoparticles. 1,48 When the images were examined, it was observed that some polymeric beads melted under the effect of electron bombardment.…”
Section: Fesem-stem Resultsmentioning
confidence: 99%
“…The faces of laponite are negatively charged while their slices are positively charged. These properties allow them to form a hydrogel with controlled gelling properties resembling a “house of cards” structure 31 …”
Section: Resultsmentioning
confidence: 99%
“…These properties allow them to form a hydrogel with controlled gelling properties resembling a "house of cards" structure. 31 Table 1 shows the calculated gelation time for each formulation using an inverted test tube. According to the obtained results, the incorporation of laponite into the chitosan decreased the gelling time of the hydrogels.…”
Section: Gelation Properties Of the Hydrogelsmentioning
confidence: 99%
“…Interestingly, the addition of nanomaterials to PEG crosslinked hydrogels can also delay the degradation rate and increase stability. Laponite is the most commonly used nanoclay, which is composed of SiO 2 , MgO, Li 2 O, Na 2 O ( Podaru et al, 2022 ). Zhai et al (2018) obtained a PEG diacrylates-clay nanocomposite hydrogel by modifying the hydroxyl group of PEG and crosslinking with nanoclay.…”
Section: Fabrication Strategy Of Peg-based Hydrogelsmentioning
confidence: 99%